2022
DOI: 10.1007/s00415-021-10948-1
|View full text |Cite
|
Sign up to set email alerts
|

Higher baseline blood glucose is associated with reduced likelihood for successful recanalization in patients with basilar artery occlusion

Abstract: Purpose Evidence regarding the effect of mechanical thrombectomy (MT) of basilar artery occlusion (BAO) stroke is yet sparse. As successful recanalization has been suggested as major determinant of outcome, the early identification of modifiable factors associated with successful recanalization could be of importance to improve functional outcome. Hyperglycemia has been associated with enhanced thrombin generation and unfavorably altered clot features. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Moreover, we also observed a higher proportion of patients with atrial fibrillation (AF) (31.5%) and a lower proportion with diabetes mellitus (39.5%) in the EVT group as compared with the non-EVT group. These observations are reflective of the general practice and are in line with the previous findings, which reported that higher blood glucose levels are associated with decreased rates of recanalization, functional outcome, and mortality [ 21 , 22 , 23 , 24 ]. Consistent with our findings, other studies have also reported a higher proportion of patients with AF undergoing EVT, probably because cardiac emboli frequently cause BAO [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we also observed a higher proportion of patients with atrial fibrillation (AF) (31.5%) and a lower proportion with diabetes mellitus (39.5%) in the EVT group as compared with the non-EVT group. These observations are reflective of the general practice and are in line with the previous findings, which reported that higher blood glucose levels are associated with decreased rates of recanalization, functional outcome, and mortality [ 21 , 22 , 23 , 24 ]. Consistent with our findings, other studies have also reported a higher proportion of patients with AF undergoing EVT, probably because cardiac emboli frequently cause BAO [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with prior studies [ 10 , 21 , 27 ], hyperglycemia on admission was not related to successful recanalization in our cohort. In contrast, a different study including 117 BAO patients (91 of which treated with MT) [ 14 ] demonstrated that lower baseline serum glucose levels were associated with successful vessel recanalization. In this study, Broocks et al.…”
Section: Discussionmentioning
confidence: 98%
“…Admission hyperglycemia was correlated with functional outcomes in patients with OTA >4.5 ​h but not in those with OTA ≤4.5 ​h. Late window patients may be most affected by glucose due to its effects on infarct growth and collaterals [ 9 , 14 ]. Further studies may illuminate the underlying causes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation